Private vegas ebook - Patterson, James (Private, 2015)
Private investigator Jack Morgan is on the hunt for a murderer in Las Vegas-and the murder ring he uncovers is unlike anything he's ever seen. Las Vegas is a city of contradictions: seedy and glamorous, secretive and wild, Vegas attracts people of all kinds-especially those with a secret to hide, or a life to leave behind. It's the perfect location for Lester Olsen's lucrative business. He gets to treat gorgeous, young women to five-star restaurants, splashy shows, and limo rides-and then he teaches them how to kill. Private Jack Morgan spends most of his time in Los Angeles, where his top investigation firm has its headquarters. But a hunt for two criminals leads him to the city of sin-and to a murder ring that is more seductively threatening than anything he's witnessed before. Chilling and marvelous, Private Vegas brings James Patterson's Private series to a sensational new level.